Risk factors, causes and hospital outcome of respiratory distress among neonates admitted in neonatal intensive care unit of a tertiary hospital - Nilufar Yeasmin; Wahida Khanam; Rubiya Parvin; Adnan, Mohammad Ahad; Md. Iqbal Hossain; Md. Tariqul Islam Mondal; Rumana Islam (International Journal of Contemporary Pediatrics, 2023)
Background: Respiratory distress is the most frequent cause of neonatal intensive care unit (NICU) admission. Despite tremendous advancement in the management, it is still a major cause perinatal deaths particularly in this part of world. Objective were to determine the risk factors, causes and outcome of respiratory distress in neonates admitted in a NICU. Methods: This cross-sectional study was carried out in NICU of institute of child and mother health, Dhaka from July 2020 to June 2021. Total 78 newborns aged below 28 days admitted with respiratory distress were enrolled. Respiratory distress was categorized as mild, moderate and severe according to Downe’s scoring. Results: Most of the babies (78.2%) belonged to age group ≤24 hours. The leading causes of distress in preterm were respiratory distress syndrome (RDS) and that in term were perinatal asphyxia (PNA) and transient tachypnoea of neonates (TTN), both with statistical significance. Pneumonia, sepsis, congenital heart disease (CHD) and meconium aspiration syndrome (MAS) were among the other important causes. There was no significant difference between mode of respiratory support and length of hospital stay with the outcome of neonates. Severe respiratory distress was significantly associated with poor outcome. Majority 64 (82.1%) of babies were discharged, 12(15.4%) neonates succumbed to death and 2(2.6%) babies were referred. Conclusions: PNA, TTN, RDS, pneumonia, sepsis, CHD and MAS were the predominant causes of NICU admission with respiratory distress. Severe respiratory distress was single most association with poor outcome.